Buenas prácticas en la educación del cuerpo en la escuela inicial y básica - Lescano, A. (Comp.) (Cuerpo, Educación y Sociedad, 2018)
This is an investigation based on three ethnographies of educational institutions with the objective of tracking good educational practices